Hyperspectral microscopy of atomically thin materials - Lim, Seungjae; Lee, Jae Ung (Current Applied Physics, 2024)
We introduce experimental configurations of hyperspectral microscopy employing atomically thin materials as an example. The optical spectrum acquired from atomically thin materials contains rich information regarding their properties, enabling nondestructive characterization. Confocal measurement schemes have been widely used to investigate atomically thin materials, offering precise spectral data from a specific sample position. However, investigating the spatial variation of optical spectrum is necessary for a comprehensive characterization. One- or two-dimensional type hyperspectral imaging provides an effective approach to analyze the spatial distribution of spectral information. In this review paper, we explain the concepts of hyperspectral imaging with several examples applied to study of atomically thin materials.
Keywords: Atomically thin material; HyperSpectral; Hyperspectral microscopy; Nondestructive characterization; Optical spectrum; Property; Spectral data; Thin materials; Two-dimensional materials; Atomically thin materials; Hyperspectral imaging; Hyperspectral microscopy; Two-dimensional materials